Influence of Handgrip Stabilization During Isokinetic Knee Strength Assessment in Older Women. Issue 4 (August 2020) - Nunes, João P.; Cunha, Paolo M.; Mayhew, Jerry L.; Ribeiro, Alex S.; Junior, Paulo S.; Fernandes, Rodrigo R.; Cyrino, Edilson S.
The present study aimed to evaluate the influence of holding the chair handles during the assessment of older women's knee flexion and extension isokinetic and isometric strength. Of 57 older women (≥60 years) selected from a convenience sample for this research, 23 were randomly chosen to perform the tests twice for reliability analyses. Each participant performed maximal isokinetic knee extension and flexion at 60°/s and 180°/s angular velocities and isometric tests under two conditions: (a) holding the lateral handle of the chair (HOLD) and (b) supporting the hands on the shoulders with the arms crossed (i.e., not holding the handle [NHOLD]). Participants performed significantly better in the HOLD compared with the NHOLD condition. Slightly lower intraclass correlation coefficients (ICC = 0.870–0.956) were noted for the HOLD than for the NHOLD condition (ICC = 0.900–0.981) so that the HOLD performance on Days 1 and 2 was different on some measures. Owing to the higher reliability coefficients in the NHOLD condition, results suggest that, when assessing knee strength in older women, the evaluee should place their hands over their shoulders with arms crossed in front of the chest (NHOLD) to maximize assessment reliability (reproducibility of performance).